Peeking beyond peaks: Challenges and research potentials of continuous multimodal multi-objective optimization - Grimme, Christian; Kerschke, Pascal; Aspar, Pelin; Trautmann, Heike; Preuss, Mike; Deutz, André H.; Wang, Hao; Emmerich, Michael (Computers & Operations Research)
Multi-objective (MO) optimization, i.e., the simultaneous optimization of multiple conflicting objectives, is gaining more and more attention in various research areas, such as evolutionary computation, machine learning (e.g., (hyper-)parameter optimization), or logistics (e.g., vehicle routing). Many works in this domain mention the structural problem property of multimodality as a challenge from two classical perspectives: (1) finding all globally optimal solution sets, and (2) avoiding to get trapped in local optima. Interestingly, these streams seem to transfer many traditional concepts of single-objective (SO) optimization into claims, assumptions, or even terminology regarding the MO domain, but mostly neglect the understanding of the structural properties as well as the algorithmic search behavior on a problem’s landscape. However, some recent works counteract this trend, by investigating the fundamentals and characteristics of MO problems using new visualization techniques and gaining surprising insights. Using these visual insights, this work proposes a step towards a unified terminology to capture multimodality and locality in a broader way than it is usually done. This enables us to investigate current research activities in multimodal continuous MO optimization and to highlight new implications and promising research directions for the design of benchmark suites, the discovery of MO landscape features, the development of new MO (or even SO) optimization algorithms, and performance indicators. For all these topics, we provide a review of ideas and methods but also an outlook on future challenges, research potential and perspectives that result from recent developments.
Keywords: Multimodal optimization; Multi-objective continuous optimization; Landscape analysis; Visualization; Benchmarking; Theory; Algorithms

On the Potential of Normalized TSP Features for Automated Algorithm Selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Proceedings of the 16$^th$ ACM/SIGEVO Conference on Foundations of genetic Algorithms (FOGA XVI))
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) a k-nearest neighbor graph (NNG) transformation of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-NNGs of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. Eventually, a proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.

Multi^3: Optimizing Multimodal Single-Objective Continuous Problems in the Multi-Objective Space by Means of Multiobjectivization - Aspar, Pelin; Kerschke, Pascal; Steinhoff, Vera; Trautmann, Heike; Grimme, Christian (Evolutionary Multi-Criterion Optimization: 11$^th$ International Conference, EMO 2021, Shenzhen, China, March 28–31, 2021, Proceedings)
In this work we examine the inner mechanisms of the recently developed sophisticated local search procedure SOMOGSA. This method solves multimodal single-objective continuous optimization problems by first expanding the problem with an additional objective (e.g., a sphere function) to the bi-objective space, and subsequently exploiting local structures and ridges of the resulting landscapes. Our study particularly focusses on the sensitivity of this multiobjectivization approach w.r.t. (i) the parametrization of the artificial second objective, as well as (ii) the position of the initial starting points in the search space. As SOMOGSA is a modular framework for encapsulating local search, we integrate Gradient and Nelder-Mead local search (as optimizers in the respective module) and compare the performance of the resulting hybrid local search to their original single-objective counterparts. We show that the SOMOGSA framework can significantly boost local search by multiobjectivization. Combined with more sophisticated local search and metaheuristics this may help in solving highly multimodal optimization problems in future.

What Is It About Humanity That We Can’t Give Away To Intelligent Machines? A European Perspective - Coombs, Crispin; Stacey, Patrick; Kawalek, Peter; Simeonova, Boyka; Becker, Jörg; Bergener, Katrin; Carvalho, João Álvaro; Fantinato, Marcelo; Garmann-Johnsen, Niels F.; Grimme, Christian; Stein, Armin; Trautmann, Heike (International Journal of Information Management)
One of the most significant recent technological developments concerns the development and implementation of ‘intelligent machines’ that draw on recent advances in artificial intelligence (AI) and robotics. However, there are growing tensions between human freedoms and machine controls. This article reports the findings of a workshop that investigated the application of the principles of human freedom throughout intelligent machine development and use. Forty IS researchers from ten different countries discussed four contemporary AI and humanity issues and the most relevant IS domain challenges. This article summarizes their experiences and opinions regarding four AI and humanity themes: Crime & conflict, Jobs, Attention, and Wellbeing. The outcomes of the workshop discussions identify three attributes of humanity that need preservation: a critique of the design and application of AI, and the intelligent machines it can create; human involvement in the loop of intelligent machine decision-making processes; and the ability to interpret and explain intelligent machine decision-making processes. The article provides an agenda for future AI and humanity research.

Towards Feature-Free Automated Algorithm Selection for Single-Objective Continuous Black-Box Optimization - Prager, Raphael Patrick; Vinzent Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (2021 IEEE Symposium Series on Computational Intelligence (SSCI))
We propose a novel method for automated algorithm selection in the domain of single-objective continuous black-box optimization. In contrast to existing methods, we use convolutional neural networks as the selection apparatus which bases its decision on a so-called ‘fitness map’. This fitness map is a 2D representation of a two dimensional search space where different gray scales indicate the quality of found solutions in certain areas. Our devised approach uses a modular CMA-ES framework which offers the option to create the conventional CMA-ES, CMA-ES with the alternate step-size adaptation and many other variants proposed over the years. In total, 4 608 different configurations are possible where most configurations are of complementary nature. In this proof-of-concept work, we consider a subset of 32 possible configurations. The developed method is evaluated against an excerpt of BBOB functions and its performance is compared against baselines that are commonly used in automated algorithm selection - the best standalone algorithm (configuration) and the best obtainable sequence of configurations. While the results indicate that the use of the fitness map is not superior on every benchmark problem, it indubitably shows its merit on more hard-to-solve problems. This offers a promising perspective for generalizing to other types of optimization problems and problem domains.

RP-Mod & RP-Crowd: Moderator- and Crowd-Annotated German News Comment Datasets - Assenmacher, Dennis; Niemann, Marco; Müller, Kilian; Seiler, Moritz V.; Riehle, Dennis M.; Trautmann, Heike (Proceedings of the Neural Information Processing Systems Track on Datasets and Benchmarks 1 (NeurIPS Datasets and Benchmarks 2021))
Abuse and hate are penetrating social media and many comment sections of news media companies. These platform providers invest considerable efforts to mod- erate user-generated contributions to prevent losing readers who get appalled by inappropriate texts. This is further enforced by legislative actions, which make non-clearance of these comments a punishable action. While (semi-)automated solutions using Natural Language Processing and advanced Machine Learning techniques are getting increasingly sophisticated, the domain of abusive language detection still struggles as large non-English and well-curated datasets are scarce or not publicly available. With this work, we publish and analyse the largest annotated German abusive language comment datasets to date. In contrast to existing datasets, we achieve a high labelling standard by conducting a thorough crowd-based an- notation study that complements professional moderators’ decisions, which are also included in the dataset. We compare and cross-evaluate the performance of baseline algorithms and state-of-the-art transformer-based language models, which are fine-tuned on our datasets and an existing alternative, showing the usefulness for the community.

Gender and Authority – The Entanglement of Two Concepts in High Medieval Historiography - Foerster, Anne (Geschlecht macht Herrschaft – Interdisziplinäre Studien zu vormoderner Macht und Herrschaft / Gender Power Sovereignty – Interdisciplinary Studies on Premodern Power)

Die Witwenschaft kinderloser Königinnen im Hochmittelalter - Foerster, Anne (Kinderlosigkeit im Mittelalter)

Erklärvideos in der Sprachwissenschaft – Sprache-Bild-Bezüge und ihr Einfluss auf den Lernerfolg (die hochschullehre – Jahrgang 7-2021)

A Database for Research on Detection and Enhancement of Speech Transmitted over HF links - Heitkaemper, Jens; Schmalenstroeer, Joerg; Ion, Valentin; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

How entrepreneur’s leadership behavior and demographics shape applicant attraction to new ventures: the role of stereotypes - Hubner-Benz, Sylvia; Rudic, Biljana; Baum, Matthias (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

An Asia-centric approach to team innovation: Cultural differences in exploration and exploitation behavior - Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli; Tripathi, Neha; Kaschner, Tamara; Le Kong, Xing (Journal of Business Research)
Keywords: Marketing

Introduction - Jacob, Joachim; Süßmann, Johannes (The Reception of Antiquity in the Age of Enlightenment. English Edition ed. by Christina C. Harker. Translated by Duncan Alexander Smart)

Investigating students' processes of noticing and interpreting syntactic language features in word problem solving through eye-tracking - Dröse, Jennifer; Prediger, S.; Neugebauer, P.; Danhier, R. D.; Mertins, B. (International Electronic Journal of Mathematics Education, 16(1), em0625)

Identifying obstacles is not enough for everybody – Differential efficacy of an intervention fostering fifth graders’ comprehension for word problems - Dröse, Jennifer; Prediger, S. (Studies in Educational Evaluation, 68 (100953))

Prokrastination bei Studierenden verringern durch Anwendung eines Ratgebers im Gruppensetting - Korsmeier, Teresa; Bobe, Julia; Klingsieck, Katrin B. (Zeitschrift für Beratung und Studium)

"Welcome to Night Vale" und/mit Derrida: Lernen, mit den Gespenstern zu leben? - Spener, Anna Maria (Literatur und das Böse. Beiträge des 10. Studierendenkongress Komparatistik)

"Meine Trauer war (k)eine Krankheit"? Achronologisches Erzählen einer anhaltenden Trauerstörung in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" - Spener, Anna Maria (Anafora. Zeitschrift für Literaturwissenschaft)

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education - Scheunemann, Anne; Schnettler, Theresa; Bobe, Julia; Fries, Stefan; Grunschel, Carola (European Journal of Psychology of Education)
Abstract Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The present three-wave longitudinal study explored the reciprocal relationships between academic procrastination, study satisfaction, and dropout intentions over one semester. To this end, we used data of N = 326 undergraduate students enrolled in mathematics and law. Our latent cross-lagged panel model replicated existing empirical cross-sectional findings between the variables (i.e., academic procrastination, study satisfaction, and dropout intentions). Regarding the longitudinal relations, as expected, the cross-lagged effects showed that higher dropout intentions significantly related to subsequent higher academic procrastination and lower study satisfaction. Unexpectedly, academic procrastination did not significantly relate to subsequent dropout intentions. Additionally, higher study satisfaction significantly associated with subsequent higher dropout intentions—possibly due to unfulfilled expectations. Further, higher study satisfaction significantly related to subsequent higher procrastination—possibly due to more confidence among satisfied students. Our results broaden the view on dropout intentions as part of the dynamic interplay of student dropout determinants and the need to refine dropout models’ assumptions accordingly. Practically, realistic expectations seem important to reduce dropout intentions. Further, student counselors should have a closer look at the reasons for academic procrastination to develop individual solutions for this dysfunctional behavior.
Keywords: Developmental and Educational Psychology; Education

Digitales Praxissemester - kann das überhaupt gut gehen? - Göddertz, Nina (Care Work in der gesellschaftlichen Transformation. Beschäftigung, Bildung, Fachdidaktik)
Marianne Friese/Rita Braches-Chyrek Einführung Marianne Friese Care Work im Spannungsfeld gesellschaftlicher Transformation. Systemische Widersprüche und Entwicklungsperspektiven Berufliche Bildung und Beschäftigungssysteme Denise Becka und Michaela Evans Wohlfahrtsproduktion und Care im digitalen Wandel: Perspektiven für Beruflichkeit in der Pflege Heidrun Herzberg und Peter Alheit Zur Akzeptanz des Konzepts „Community Nurse" im Land Brandenburg: Eine qualitative Vorstudie Karin Reiber, Jan Braun und Jutta Mohr Berufliche Bildung in der Domäne Pflege zwischen Anforderungen des Beschäftigungssystems und individueller berufsbiografischer Entwicklung Philipp Struck Entwicklungs- und Verbesserungsperspektiven für berufliche (Aus-)Bildungsprozesse im Gesundheitswesen Rita Braches-Chyrek Soziale Arbeit: Ausbildung und Beschäftigung Julia Kastrup und Alexandra Brutzer Hauswirtschaft in Zeiten von Corona - Ergebnisse einer Interviewstudie mit Hauswirtschaftlichen Fachkräften Akademische Bildung und Weiterbildung Anna Bobe, Anke Karber und Tobias Moock Theorie und Praxis in sozialpädagogischen Bildungsgängen - Erste Strukturierungsansätze vielfältiger Verhältnisse Manuela Liebig, Mirjam Chris und Annemarie Marx „Am Ball bleiben" - Sensibilisierung für aktuelle Herausforderungen der sozialpädagogischen Praxis durch Arbeitsanalysen im Lehramtsstudium für berufliche Schulen Anja Walter, Martin Fritzenwanker, Martin Karstädt Von Berufsfeldanalysen zum Unterricht - empirisches Material für die Bildungspraxis im Berufsfeld Gesundheit und Pflege nutzen Nina Göddertz „Digitales Praxissemester - kann das überhaupt gut gehen?" - Reflexionen von Lehramtsstudierenden vor und während des Praxissemesters in Zeiten der Covid-19-Pandemie Stephanie Spanu Systemrelevant(e) ausbilden. Berufliches Lehramt, Fachrichtung Sozialpädagogik und die berufliche Bildung: Der Fachkräftemangel als gesellschaftliche Aufgabe Julia Kastrup, Birgit Peuker, Marie Nölle-Krug und Simon Vollmer Gemeinsam innovativ! - Transformative Themenfelder in der lehramtsbezogenen Ausbildung der beruflichen Fachrichtung Ernährung- und Hauswirtschaft standortübergreifend lehren und lernen Ursula Walkenhorst, Annika Lara Schwarze Digitale Transformation in der Hochschullehre - Chancen und Grenzen für die Gesundheitsberufe Dana Bergmann und Astrid Seltrecht Weiterbildungsordnungsarbeit für Pflegeberufe Claudia Schepers, Johanna Krawietz und Jella Fuchs Kollegiale Beratung für die Kitteltasche
Keywords: Modernisierung personenbezogener Dienstleistungsberufe Aktueller Forschungsstand; Best Practice und Desiderata

A Comparison and Combination of Unsupervised Blind Source Separation Techniques - Boeddeker, Christoph; Rautenberg, Frederik; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised blind source separation methods do not require a training phase and thus cannot suffer from a train-test mismatch, which is a common concern in neural network based source separation. The unsupervised techniques can be categorized in two classes, those building upon the sparsity of speech in the Short-Time Fourier transform domain and those exploiting non-Gaussianity or non-stationarity of the source signals. In this contribution, spatial mixture models which fall in the first category and independent vector analysis (IVA) as a representative of the second category are compared w.r.t. their separation performance and the performance of a downstream speech recognizer on a reverberant dataset of reasonable size. Furthermore, we introduce a serial concatenation of the two, where the result of the mixture model serves as initialization of IVA, which achieves significantly better WER performance than each algorithm individually and even approaches the performance of a much more complex neural network based technique.

Convolutive Transfer Function Invariant SDR Training Criteria for Multi-Channel Reverberant Speech Separation - Boeddeker, Christoph; Zhang, Wangyou; Nakatani, Tomohiro; Kinoshita, Keisuke; Ochiai, Tsubasa; Delcroix, Marc; Kamo, Naoyuki; Qian, Yanmin; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Open Range Pitch Tracking for Carrier Frequency Difference Estimation from HF Transmitted Speech - Schmalenstroeer, Joerg; Heitkaemper, Jens; Ullmann, Joerg; Haeb-Umbach, Reinhold (29th European Signal Processing Conference (EUSIPCO))

Rezension von: Jörg van Norden, Thomas Must, Lars Deile, Peter Riedel, Susan Krause und Wanda Schürenberg (Hgg.): Geschichtsdidaktische Grundbegriffe. Ein Bilderbuch für Studium, Lehre und Beruf. Hannover 2020 - Hartung, Olaf (H-Soz-Kult)

Geometry calibration in wireless acoustic sensor networks utilizing DoA and distance information - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (EURASIP Journal on Audio, Speech, and Music Processing)
Due to the ad hoc nature of wireless acoustic sensor networks, the position of the sensor nodes is typically unknown. This contribution proposes a technique to estimate the position and orientation of the sensor nodes from the recorded speech signals. The method assumes that a node comprises a microphone array with synchronously sampled microphones rather than a single microphone, but does not require the sampling clocks of the nodes to be synchronized. From the observed audio signals, the distances between the acoustic sources and arrays, as well as the directions of arrival, are estimated. They serve as input to a non-linear least squares problem, from which both the sensor nodes’ positions and orientations, as well as the source positions, are alternatingly estimated in an iterative process. Given one set of unknowns, i.e., either the source positions or the sensor nodes’ geometry, the other set of unknowns can be computed in closed-form. The proposed approach is computationally efficient and the first one, which employs both distance and directional information for geometry calibration in a common cost function. Since both distance and direction of arrival measurements suffer from outliers, e.g., caused by strong reflections of the sound waves on the surfaces of the room, we introduce measures to deemphasize or remove unreliable measurements. Additionally, we discuss modifications of our previously proposed deep neural network-based acoustic distance estimator, to account not only for omnidirectional sources but also for directional sources. Simulation results show good positioning accuracy and compare very favorably with alternative approaches from the literature.

Iterative Geometry Calibration from Distance Estimates for Wireless Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

On Source-Microphone Distance Estimation Using Convolutional Recurrent Neural Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

Online Estimation of Sampling Rate Offsets in Wireless Acoustic Sensor Networks with Packet Loss - Chinaev, Aleksej; Enzner, Gerald; Gburrek, Tobias; Schmalenstroeer, Joerg (29th European Signal Processing Conference (EUSIPCO))

Seelsorge der Geschichte? Konfessionelle Geschichtspolitik im 17. Jahrhundert am Beispiel der Monumenta Paderbornensia Ferdinands von Fürstenberg - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Forschungsperspektiven - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Zum Paradigma der Konfessionalisierung - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

A. Seidler, I. Monok (Hgg.): Reformation und Bücher. Zentren der Ideen – Zentren der Buchproduktion. Wiesbaden 2020 - Moritz, Tilman (sehepunkte)

Das Commentariolum Ferdinands von Fürstenberg – eine lateinisch-deutsche Synopse - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit

Max Schulze vs. Joana Dahlhoff - Schulze, Max (Joana Dahlhoff: Recherche patiente)

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

Contrastive Predictive Coding Supported Factorized Variational Autoencoder for Unsupervised Learning of Disentangled Speech Representations - Ebbers, Janek; Kuhlmann, Michael; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
In this work we address disentanglement of style and content in speech signals. We propose a fully convolutional variational autoencoder employing two encoders: a content encoder and a style encoder. To foster disentanglement, we propose adversarial contrastive predictive coding. This new disentanglement method does neither need parallel data nor any supervision. We show that the proposed technique is capable of separating speaker and content traits into the two different representations and show competitive speaker-content disentanglement performance compared to other unsupervised approaches. We further demonstrate an increased robustness of the content representation against a train-test mismatch compared to spectral features, when used for phone recognition.

Human Factors in Secure Software Development - Acar, Yasemin

A Large-Scale Interview Study on Information Security in and Attacks against Small and Medium-sized Enterprises - Huaman, Nicolas; von Skarczinski, Bennet; Stransky, Christian; Wermke, Dominik; Acar, Yasemin; Dreißigacker, Arne; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Why Eve and Mallory Still Love Android: Revisiting TLS (In)Security in Android Applications - Oltrogge, Marten; Huaman, Nicolas; Amft, Sabrina; Acar, Yasemin; Backes, Michael; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Passivität als Widerstand gegen die Macht der Verhältnisse? Melvilles Bartleby, the scrivener aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute)

Happy clappy heile Welt? Wie angesichts von Krisen und Katastrophen eine schöne Welt besungen werden kann - Neumann, Anna (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

This is my Fight Song - Neumann, Anna; Katharina, Kammeyer; Vera, Uppenkamp (Musk als Lebensmittel)

Keller, Raabe, Fontane: ›nichts für den Durchschnittsleser‹. Miszellane Lektüren, ›imaginäre Leser‹ und Kanonisierungsprozesse in der Literaturkritik der zeitgenössischen Presse - Gretz, Daniela (Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert)

Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert

Mit Aufgaben im inklusiven Mathematikunterricht professionell umgehen - Erkenntnisse einer Interviewstudie mit Lehrpersonen der Sekundarstufe - Häsel-Weide, Uta; Seitz, Simone; Wallner, Melina; Wilke, Yannik; Heckmann, Lara (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Conceptualiziation processes of 6th graders for rotational symmetry - Hattermann, Mathias; Häsel-Weide, Uta; Wallner, Melina (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Zusammenhang zwischen familiären Lebenssituationen und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter. - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators